Impact of the ASPECT scores and distribution on outcome among patients undergoing thrombectomy for acute ischemic stroke. (10th June 2014) - Spiotta, Alejandro M; Vargas, Jan; Hawk, Harris; Turner, Raymond; Chaudry, M Imran; Battenhouse, Holly; Turk, Aquilla S
Abstract : Introduction: This study investigates whether the Alberta Stroke Program Early CT Score (ASPECTS) quantification is associated with outcome following mechanical thrombectomy. Objective: To determine whether preintervention non-perfect ASPECT scores involving cortical or subcortical regions and the side of the non-perfect ASPECT score affects outcomes. Methods: A retrospective review of a prospectively maintained database of patients with acute ischemic stroke involving the anterior circulation who underwent thrombectomy between May 2008 and August 2012 at a single tertiary care center. The device for mechanical thrombectomy used was the penumbra aspiration system (Penumbra Inc, Alameda, California, USA) and the Solitaire stent retriever (ev3, Irvine, California, USA). A 'blinded' neuroradiologist obtained ASPECTS quantification and noted each region demonstrating early changes. Results: 149 patients (51.7% female, mean age 66.1±15.1 years) were included with an average National Institutes of Health Stroke Scale of 16.2±6.7. Patients with non-perfect ASPECT scores on pretreatment imaging were more likely to have a hemorrhagic conversion (p=0.04) evident on post-procedure CT. However, functional outcomes were the same. Patients with both cortical and basal ganglia non-perfect ASPECT scores were more likely to be in a persistent vegetative state or expire. No differences were identified in outcome among patients with left- versus right-sided infarcts affecting the basal ganglia or cortical regions. Conclusions: These findings support a strategy of selecting candidacy for thrombectomy that does not exclude patients with non-perfect ASPECT scores involving either the basal ganglia or cortical regions. Outcomes were identical among patients with no non-perfect ASPECT scores and those with cortical or subcortical infarcts, despite a higher incidence of hemorrhagic conversion found among those with non-perfect ASPECT scores.